Implementation of Continuing Professional Development in Self Professional Development Factors Amongst Aviation Polytechnic’s Lecturers - Andrian Pratama; Muchlas Samani; Asto Buditjahjanto (Asian Journal of Social and Humanities, 2024)
The purpose of this research is to find out the picture of conditions in quantity and quality of lecturers today and the implementation of continuing professional develompent lecturers in terms of self professional  development at makassar aviation polytechnic. This research uses a qualitative approach by collecting data in terms of documents, literature, and interviews. The research subject was a makassar aviation polytechnic lecturer who numbered 16 people supported by interviews with 3 people in managerial positions. The implementation of the factors studied is the implementation factor of continuing professional develompent lecturers in terms of self professional development.  The results of this study show that the implementation of  Continuing Professional Development  in  aviation polytechnics is still not optimal in terms of quantity. This can be seen from the number of certified lecturers as many as 7 people or 43% of the number of permanent lecturers.  Aviation polytechnics do  not yet have lecturers  with  doctoral criteria. There are variables of self professional development, namely in the implementation of  Continuing Professional Development in self reading activities  are considered  good, self development in research activities  is considered not optimal, and in academic quality activities  is considered  Not optimal. These findings indicate that implementation of  Continuing Professional Development has not been optimal.